Impact of educational intervention on oral health knowledge among AYUSH workers in Sriganganagar, Rajasthan - A quasi experimental study - Parul Sharma; Simarpreet Singh; Anmol Mathur; Manu Batra; Vikram Pal Aggarwal; Mankirat Kaur Gill (Wolters Kluwer Medknow Publications, 2020)
Background: Young children receive no dental care though they are frequently visiting AYUSH workers for routine medical check-ups. These checks-ups can be integrated with oral health to uplift the oral health status of children by taking advantage of an existing network of the workforce who has made roots into the existing society. Aims: The aim of this study was to assess the impact of educational intervention on oral health knowledge among AYUSH workers. Materials and Methods: Quasi-experimental study design was used among AYUSH workers registered under RBSK program in the Ganganagar district. A close-ended questionnaire was prepared. The intervention was carried out by a PowerPoint presentation regarding oral health after data collection. The same questionnaire was mailed again to the doctors after 1 month, with 1-week duration to respond back. Statistical analysis was performed using Chi-square and paired t-test using SPSS v22. Chi-square and paired t-test were used for analysis. P value was considered significant at <0.05. Results: Posttest analyses showed an overall increase in the knowledge level of AYUSH health care workers with a mean 13.22 ± 1.40, which was highly significant (P < 0.001), whereas the mean pretest score was 8.37 ± 2.8. Conclusion: The utilization of AYUSH health care workers at the grass root level can be used to provide basic oral health education to the general population in rural areas where the dentist-to-population ratio is low.